The Role of School Libraries as Teaching and Learning Resources - Tridana, Anggi; Vlora, Rani Kurnia (JIPI (Jurnal Ilmu Perpustakaan dan Informasi), 2024)
A library is a work unit of an institution that contains a collection of books to support increasing learning resources that are arranged to be read, studied and used as reference materials. It is impossible for an educational institution to run well if the teachers and students are not supported by the learning resources needed to carry out teaching and learning activities. The purpose of this research is to look at the role of the library as a teaching and learning resource for students and teaching staff at SMPN 2 South Pemulutan. The research method used is descriptive research with a case study type that will be carried out on the role of the library at SMPN 2 South Pemulutan as a source of teaching and learning in schools. Data collection techniques through observation, interviews and documentation. The informants in this research were library users at SMPN 2 South Pemulutan, namely students, and teachers or education staff. The results of the research state that the SMPN 2 South Pemulutan Library has an important role as an institution that provides knowledge and information to its parent institution and its user community. The SMPN 2 Pemulutan Selatan library facilitates students and teachers or education staff (GTK) with services at the library. Teaching and learning activities are also often carried out in the library of SMPN 2 Pemulutan Selatan. There are several teaching staff who use the library as a means for "moving classes". With the aim that students do not feel bored and bored if they only study in the classroom. The library is a source of knowledge and a center for learning activities as well as a source of new ideas that can encourage students' willingness to think rationally, students can search for the information they need and there can be synergy between librarians and students which will result in student achievement. Also good performance for librarians so that libraries play a very important role in improving student learning achievement because they can make their users smarter, especially in producing students who excel.